Desktop-Based AHP Application Development for SMEs Promotion Media Decision Support System (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Promotion media is an important part of product marketing in SMEs. Promotions are carried out to increase product sales volume from the target set by SMEs. SMEs in promoting using social media, print media, television, search engines, and product collaboration. For promotion to be more efficient, it is necessary to know the most effective promotional media. One of the decision support methods that can be used to overcome these problems is the Analytic Hierarchy Process (AHP) method. The data was obtained from the distribution of questionnaires from related SMEs. The AHP for SMEs application is a desktop-based application with a Windows operating system. This application was developed using Visual Basic programming language with MySQL database. The AHP SMEs application can be installed on laptop/pc devices with 32-bit or 64-bit Windows operating systems. The AHP SMEs application focuses on completing alternative choices of promotional media based on criteria that have been determined by the user. While the method in completing the alternative choice uses the Analytic Hierarchy Process (AHP). The results of this study indicate that the first promotion media is social media, then product collaboration, search engines, television, and the last is print media.